2011
DOI: 10.1007/s12008-011-0132-x
|View full text |Cite|
|
Sign up to set email alerts
|

Biomechanically-based motion control for a digital human

Abstract: An algorithm for both human-like motion generation and joint torques computation for digital humans is addressed in this paper. This goal has been achieved using techniques derived from robotics. In particular, the so-called augmented Jacobian has been used to solve the inverse kinematics problem with a single closed loop inverse kinematics algorithm. Furthermore, a position control for the center of mass of the kinematic chain, and for its projection on the support plane (center of pressure), has been impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Два последних уравнения являются уравнениями для условий устойчивости, и на настоящий момент не разработано методов точного численного решения (2) с учетом связей такого типа, содержащих вторые производные от координат системы. В существующих работах [8][9][10], как правило, учитывается только уравнение (2д) в упрощенном виде. В настоящей работе из уравнения (2д) исключаются члены со вторыми производными.…”
Section: синтез управляемого движенияunclassified
“…Два последних уравнения являются уравнениями для условий устойчивости, и на настоящий момент не разработано методов точного численного решения (2) с учетом связей такого типа, содержащих вторые производные от координат системы. В существующих работах [8][9][10], как правило, учитывается только уравнение (2д) в упрощенном виде. В настоящей работе из уравнения (2д) исключаются члены со вторыми производными.…”
Section: синтез управляемого движенияunclassified
“…For the evaluation of the interaction with people, the use of manikins is necessary. Recent studies have shown some advantages of using manikins in a virtual environment and for the simulation of human tasks (Di Gironimo et al, 2012a;Di Gironimo et al, 2012d).…”
Section: Ergonomic Analysis and Evaluation Of Concept Characteristicsmentioning
confidence: 99%
“…For the evaluation of the interaction with people, the use of manikins is necessary. Recent studies have shown some advantages of using manikins in a virtual environment and for the simulation of human tasks (Di Gironimo et al, 2012a;Di Gironimo et al, 2012d).…”
Section: Ergonomic Analysis and Evaluation Of Concept Characteristicsmentioning
confidence: 99%